2020
DOI: 10.48550/arxiv.2008.00127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial identification and dependence-robust confidence intervals for capture-recapture surveys

Abstract: Capture-recapture (CRC) surveys are widely used to estimate the size of a population whose members cannot be enumerated directly. When k capture samples are obtained, counts of unit captures in subsets of samples are represented naturally by a 2 k contingency table in which one element -the number of individuals appearing in none of the samples -remains unobserved. In the absence of additional assumptions, the population size is not point-identified. Assumptions about independence between samples are often use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The other option is to study LCMs through the framework of partial identification (Tamer, 2010;Gustafson, 2010), which was recently used in multiple-systems estimation by Sun et al (2020) for frequentist inference for partially-identified log-linear models. This would require both: 1) a better technical understanding of what parameters, or functions of parameters, of LCMs are not identified, and 2) placing substantively meaningful priors on the non-identified parameters (i.e.…”
Section: C5 Takeawaysmentioning
confidence: 99%
“…The other option is to study LCMs through the framework of partial identification (Tamer, 2010;Gustafson, 2010), which was recently used in multiple-systems estimation by Sun et al (2020) for frequentist inference for partially-identified log-linear models. This would require both: 1) a better technical understanding of what parameters, or functions of parameters, of LCMs are not identified, and 2) placing substantively meaningful priors on the non-identified parameters (i.e.…”
Section: C5 Takeawaysmentioning
confidence: 99%